2021
DOI: 10.1039/d0ta10785a
|View full text |Cite
|
Sign up to set email alerts
|

Readily useable bulk phenoxazine-based covalent organic framework cathode materials with superior kinetics and high redox potentials

Abstract: Redox-active covalent organic frameworks (COFs) with dense redox sites are promising electrical energy storage materials with robust architectures, high surface areas, insolubility in electrolytes, and open pores for electrolyte transportation,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…There has been active research for developing new COFs with novel molecular configurations that are dedicated to battery electrode applications. 106,107,113,114 For instance, Yang et al reported COFs based on 2,7-diaminobenzo[lmn] [3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone (DANT) and two different linker, namely 1,3,5-triformylphloroglucinol (Tp) and 1,3,5-triformylbenzene (Tb). 106 The COF integrated with Tb linker showed superior electrochemical performance in many aspects, including specific capacity, rate-performance, and cycling stability, although the molecular weights of the two linkers are very similar.…”
Section: Molecular Designmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been active research for developing new COFs with novel molecular configurations that are dedicated to battery electrode applications. 106,107,113,114 For instance, Yang et al reported COFs based on 2,7-diaminobenzo[lmn] [3,8]phenanthroline-1,3,6,8(2H,7H)-tetraone (DANT) and two different linker, namely 1,3,5-triformylphloroglucinol (Tp) and 1,3,5-triformylbenzene (Tb). 106 The COF integrated with Tb linker showed superior electrochemical performance in many aspects, including specific capacity, rate-performance, and cycling stability, although the molecular weights of the two linkers are very similar.…”
Section: Molecular Designmentioning
confidence: 99%
“…There has been active research for developing new COFs with novel molecular configurations that are dedicated to battery electrode applications 106,107,113,114 . For instance, Yang et al reported COFs based on 2,7‐diaminobenzo[lmn][3,8]phenanthroline‐1,3,6,8(2H,7H)‐tetraone (DANT) and two different linker, namely 1,3,5‐triformylphloroglucinol (Tp) and 1,3,5‐triformylbenzene (Tb) 106 .…”
Section: Secondary Batteriesmentioning
confidence: 99%
“…[23][24][25] Furthermore, many efforts have been devoted to developing COFs as high-performance electrode materials. [26][27][28][29] However, the reported COF electrodes often exhibit low operating voltage (o3 V), [30][31][32] which is a bottleneck for their further development. Only a few redox organic groups in amorphous materials were reported for high-voltage lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the two phenoxazinebased p-type COFs both exhibit high discharge voltages of ∼3.6 V (vs Li + /Li). 28 However, p-type COFs rely on anions from the electrolyte to compensate charges during charge processes. Thus, large amounts of electrolyte need to be used to ensure a smooth charge process, which inevitably lowers the whole energy density of batteries with p-type COFs and restricts practical applications.…”
mentioning
confidence: 99%
“…The p-type COFs featuring conversion between neutral and positive state during redox processes generally show higher voltage above 3 V (vs Li + /Li). For example, the two phenoxazine-based p-type COFs both exhibit high discharge voltages of ∼3.6 V (vs Li + /Li) . However, p-type COFs rely on anions from the electrolyte to compensate charges during charge processes.…”
mentioning
confidence: 99%